Uji Efektivitas Antibakteri Larutan Lo’i Keta Dan Ekstrak Metanol Lo’i Keta Terhadap Pertumbuhan Bakteri Staphylococcus aureus dan Streptococcus pyogenes - Adelia, Fadiah; Musyarrafah; Rozikin; Lestari, Novianti Anggie (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to stimulate the effectiveness of antibacterial solutions and methanol extracts of lo'i keta, a traditional medicine from Bima-Dompu, West Nusa Tenggara, against the growth of both bacteria. Lo'i keta solutions and methanol extracts were tested at concentrations of 25%, 50%, 75%, and 100% using the agar well diffusion method. The inhibition zones formed were measured to assess antibacterial activity. Ciprofloxacin was used as a positive control, and distilled water as a negative control. The results showed that lo'i keta solutions and methanol extracts had inhibitory power against Staphylococcus aureus and Streptococcus pyogenes. Its effectiveness increased with increasing concentrations of the solution and extract. The best activity was shown at a concentration of 100%, approaching the positive control. This study shows that lo'i keta has the potential as a natural alternative to fight gram-positive bacteria, because resistance to antibiotics is increasing and lo'i keta can be used as a traditional herbal medicine, but there has not been much scientific exploration.